LEGITIMACIÓN ACTIVA EN LOS PROCESOS COLECTIVOS A TENOR DEL CRITERIO - Masciotra, Mario; Falke, Dr. Ignacio Agustín (Revistas ICDP, 2015)
LEGITIMACIÓN ACTIVA EN LOS PROCESOS COLECTIVOS A TENOR DEL CRITERIO